2017
DOI: 10.1111/ejh.12881
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measures for adult and pediatric hemophilia patients with inhibitors

Abstract: Recent advancements in almost all aspects of hemophilia treatment have vastly improved patient care and management, and new and emerging treatments hold the promise of further progress. However, there remains a scarcity of data on long-term outcomes in hemophilia, particularly among those patients with inhibitors, for whom no validated outcome assessment tools are currently available. At the 15 th ZürichHaemophilia Forum, an expert panel reviewed the most important outcome measures in inhibitor patients and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…In addition, there is ongoing discussion about the optimal outcome measure and suitability of ABR as an efficacy measure in patients with hemophilia with and without inhibitors. [11][12][13][14][15] In the European Medicine Agency (EMA) guidelines on core summary of product characteristics for human plasma derived and recombinant coagulation factor FVIII and FIX products, it is stated that ABR is not comparable between different factor concentrates and between different clinical studies. 16,17 This statement has been introduced empirically based on the long-standing experience in the regulation of hemophilia therapeutics, however, there is lack of supportive and published evidence.…”
Section: Annual Bleeding Rates In Hemophilia Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is ongoing discussion about the optimal outcome measure and suitability of ABR as an efficacy measure in patients with hemophilia with and without inhibitors. [11][12][13][14][15] In the European Medicine Agency (EMA) guidelines on core summary of product characteristics for human plasma derived and recombinant coagulation factor FVIII and FIX products, it is stated that ABR is not comparable between different factor concentrates and between different clinical studies. 16,17 This statement has been introduced empirically based on the long-standing experience in the regulation of hemophilia therapeutics, however, there is lack of supportive and published evidence.…”
Section: Annual Bleeding Rates In Hemophilia Patientsmentioning
confidence: 99%
“…It has been demonstrated that there is a substantial range of bleeding frequencies among patients with similar clotting factor levels, confirming the ABR as a more personalized parameter. In addition, there is ongoing discussion about the optimal outcome measure and suitability of ABR as an efficacy measure in patients with hemophilia with and without inhibitors 11–15 . In the European Medicine Agency (EMA) guidelines on core summary of product characteristics for human plasma derived and recombinant coagulation factor FVIII and FIX products, it is stated that ABR is not comparable between different factor concentrates and between different clinical studies 16,17 .…”
mentioning
confidence: 99%
“…Already, an abundance of tools exists to measure a variety of outcomes, such as joint health status, 13 QoL, 14 activities and participation, 13,15 as well as outcomes specifically for people with inhibitors. 16 However, the quality of these tools differs as well as their availability and applicability globally. 14,15 Therefore, standardization of which tools to use is being advocated.…”
Section: Functional Outcomes Andmentioning
confidence: 99%
“…Then, these outcomes should be measured appropriately. Already, an abundance of tools exists to measure a variety of outcomes, such as joint health status, QoL, activities and participation, as well as outcomes specifically for people with inhibitors . However, the quality of these tools differs as well as their availability and applicability globally .…”
mentioning
confidence: 99%
“…Furthermore, disease-specific questionnaires do not easily allow comparisons between population-based health measures or population-wide health assessments, and they can impede the conduct of comparative cost-benefit and cost-effectiveness analyses [11]. In such situations or when comparisons with patients with other disorders are warranted [12], generic HRQoL measures may add useful information to or partially replace disease-specific health measures. But generic health status measures also have limitations when applied to longitudinal research involving different age groups, especially when studying longitudinal changes of HRQoL through childhood and adolescence into adulthood.…”
Section: Introductionmentioning
confidence: 99%